The Effect of Filter Media Size and Loading Rate to Filter Performance of Removing Microplastics using Rapid Sand Filter - Mutiara Fajar; Emenda Sembiring; Marisa Handajani (Journal of Engineering and Technological Sciences, 2022)
Microplastics (MP) can pose a serious threat to the environment and human health because of their tiny size and ability to spread easily in water. One of the alternative treatments to remove MP from water is the rapid sand filter (RSF). The objective of this study was to analyze the effects of filter media size and loading rate on RSF performance in removing MP. The applied filter media was silica sand with effective sizes (ES) of 0.39 and 0.68 mm. The loading rates of filtration were 4; 6; 8 and 10 m3/m2-h. The MP samples were made from plastic bags and torn tires (artificial samples: 10 to 800 µm). This study showed that the MP removal percentage was up to 96.6% (MP size larger than 200 µm). The head loss increment for loading rates 4; 6; 8; 10 m3/m2-h was 0.16; 0.35; 0.34; 0.25 m (ES 0.39 m) and 0.10; 0.18; 0.18; 0.19 m (ES 0.68 m)), respectively. Meanwhile, the filtration cycle for loading rates 4; 6; 8; and 10 m3/m2-h was 5, 2, 2, and 1 days (ES 0.39 mm) and 9, 4, 3, and 3 days (ES 0.68 mm), respectively. The result of this study showed that the smaller the filter media size, the higher the head loss of the filter media bed. Furthermore, there is an increased head loss of the filter media bed when the loading rate is greater.